2003
DOI: 10.1021/la035396h
|View full text |Cite
|
Sign up to set email alerts
|

Polyetheretherketone (PEEK) Surface Functionalization by Low-Energy Ion-Beam Irradiation under a Reactive O2 Environment and Its Effect on the PEEK/Copper Adhesives

Abstract: A low-energy Ar+ ion beam was used to modify the surface of a polyetheretherketone (PEEK) film. The modification reaction proceeded with or without oxygen gas injected during the irradiation. The surface functional groups of the modified PEEK were confirmed with X-ray photoelectron spectroscopy as increasing various oxygen-containing functional groups. The concentration of the functional groups varied rapidly with the irradiation time, reached a maximum value, and then slowly decreased. The surface morphology … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
28
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(29 citation statements)
references
References 30 publications
1
28
0
Order By: Relevance
“…The XPS spectra of PEEK exposed to ion beam radiation [9] clearly reveals the generation of new peak at 289.0 eV which corresponds to the formation of CO-O group resulting from plasma oxidation. More highly oxidized carbon increases with an increase in the O/C ratio.…”
Section: Ray Photoelectron Spectroscopy (Xps) Analysismentioning
confidence: 99%
“…The XPS spectra of PEEK exposed to ion beam radiation [9] clearly reveals the generation of new peak at 289.0 eV which corresponds to the formation of CO-O group resulting from plasma oxidation. More highly oxidized carbon increases with an increase in the O/C ratio.…”
Section: Ray Photoelectron Spectroscopy (Xps) Analysismentioning
confidence: 99%
“…[1][2][3] This material is thermally stable at the temperature of 400 C for 15 min in a nitrogen (N 2 ) atmosphere. 4,5 The melting temperature (T m ) of PEEK is in the range of 335-395 C and glass transition temperature (T g ) varies from 143 to 160 C, depending upon the grade of polymer or crystallinity.…”
Section: Introductionmentioning
confidence: 99%
“…3 In recent years, several studies have been reported the surface treated PEEK or PEEK based composites with an intention of improving adhesive bonding. 2,7 The surface modification of aryl polymers for adhesive bonding has been carried out by several techniques namely, corona discharge treatment, 1 UV/ ozone surface oxidation, 7 low-energy ion-beam irradiation under a reactive O 2 environment, etc. 1 But most of the functionalizations of aryl polymers for membrane applications have been performed through chemical methods.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Ion treatment of PEEK has been shown to induce chemical, mechanical, and electrical changes, and ion implanted PEEK has been used to create devices such as infrared bolometers. [2][3][4][5][6][7][8][9] It has also been suggested that ion implantation of PEEK and other such polymers could be used to create low cost plastic circuitry and circuit elements. 2 Photothermal spectroscopic ͑PTS͒ techniques have been extensively and successfully applied to solid state materials to obtain their thermal and optical parameters.…”
Section: Introductionmentioning
confidence: 99%